Second Five Year Plan 1956-61 - Planning Commission (Planning Commission, 1957)
On the 1st November 1954,the State of Pondicherry was transferred to India after 280 years of French occupation and became re-united with the Motherland. With the taking over of the administration, the Government of India have become fully aware of the needs of the people and the State Government have been striving to develop the State and promote the welfare of the people on a priority basis. The State of Pondicherry consists of 4 settlements covering an area of about 175 square miles with a population of 3.17 lakhs
The Development Department Government of Pondicherry